ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM KELOMPOK LQ45 DI BURSA EFEK INDONESIA - Slamet Prayogi Hatna Wijaya; Tina Sulistiyani (Universitas Ahmad Dahlan, 2012)
This study aims to determine how the influence of Earning per Share, Beta, Company Size, and dividends on stock prices LQ45 groups in Indonesia Stock Exchange, either simultaneously or partially. Factors to be the independent variable is the Earning per Share (EPS), beta (BETA), company size (SIZE), and dividends (DIV) and the dependent variable in this study is the stock price (Y). This study took data belonging to the group companies LQ45 of the year 2008-2010. Analysis tool used is Multiple Linear Regression Analysis performed using Classical Test Assumptions in advance. From the test results of Multiple Linear Regression Analysis using the Â 5%, it can be concluded that there is simultaneous influence of the EPS, BETA, SIZE, and DIV on stock prices. As for the partial regression analysis all influence on stock prices. Coefficient of determination of test results, obtained by the Adjusted R Square of 0,605.